ChemInform Abstract: Visible Light Photocatalytic Reduction of O‐Thiocarbamates: Development of a Tin‐Free Barton—McCombie Deoxygenation Reaction. Issue 10 (March 2015) - Chenneberg, Ludwig; Baralle, Alexandre; Daniel, Marion; Fensterbank, Louis; Goddard, Jean‐Philippe; Ollivier, Cyril
Abstract The photocatalyzed redox deoxygenation of o‐thiocarbamates of secondary, tertiary, and benzylic alcohols with good functional group tolerance is developed.